LANGUAGES TODAY – COMPETITION OF REGIONAL, NATIONAL AND INTERNATIONAL LANGUAGES (ON THE EXAMPLE OF GEORGIA) - Gvelesiani, Irina; Tvaltvadze, Darejan (European Scientific Journal, ESJ, 2014)
Today globalization crosses the borders of the world countries. Drastic changes are seen in different spheres of life: technology, management, information, jurisprudence, culture – everything is globalized. The ongoing processes stipulate the spread of today’s “lingva franca” (the English language) and its interference into social lives of different segments of society. Growing popularity of the English language affects state languages and the necessity of application of special policies on their defense emerges. The given paper deals with the development of the Georgian reality under the influence of the process of internationalization and a growing competitiveness of regional, national and international languages.